Sharia and death rites: The tradition of sharing kafarat rice in Tebing Tinggi Village, Kerinci - Isa, Mhd; Zufriani, Zufriani; Iskandar, Nuzul (LP3M Universitas Islam Zainul Hasan Genggong, 2025)
This study explores the tradition of beras kafarat (expiation rice) in Tebing Tinggi Village, Kerinci, as a local Islamic practice conducted by families of the deceased as a substitute for unfulfilled prayers. Using a descriptive qualitative method with a case study approach, data were collected through observations and interviews with five key informants directly involved in the tradition. Findings show that although the term kafarat in classical Islamic jurisprudence refers to specific legal penalties such as for oaths or fasting violations, the Tebing Tinggi community uses it symbolically to represent charitable acts intended to support the deceased spiritually. The practice reflects deep-rooted social solidarity and spiritual responsibility, where the act of sharing rice after Friday prayers becomes a meaningful ritual of religious and communal unity. Despite challenges from modernization and generational shifts, the tradition persists through adaptive strategies, value-based education, and community engagement. This study contributes to the discourse on Islamic law by contextualizing local cultural practices within the broader framework of sharia, highlighting the importance of preserving meaningful traditions that align with core Islamic values.